Electrocochleography During Translabyrinthine Approach for Vestibular Schwannoma Removal. Issue 3 (March 2020) - Riggs, William J.; Fitzpatrick, Douglas C.; Mattingly, Jameson K.; Harris, Michael S.; Hiss, Meghan M.; Rajkumar, Shashank; Zhan, Kevin Y.; Brown, Kevin D.; Moberly, Aaron C.; Dodson, Edward E.; Adunka, Oliver F.
Abstract : Hypothesis: Intraoperative electrocochleography (ECochG) can differentiate hair cell and neural dysfunction caused by a vestibular schwannoma (VS) and help define the site of lesion as peripheral or central to the spiral ganglion. Background: Hearing loss in patients with a VS can be caused by both sensory (cochlear) and neural dysfunction. Methods: Round-window ECochG using low and high-frequency tone bursts was performed in 49 subjects with a VS. Responses were analyzed for magnitude, spectrum, and shape of the time waveform. Components examined included the cochlear microphonic, auditory nerve neurophonic, compound action potential (CAP), and summating potential (SP). Results: Variability in the summed response magnitudes across frequency, or "total response" (ECochG-TR), varied from 0.1 to 100 μV. Responses were larger for lower frequencies. Subjective estimates revealed a wide range of neural contributions from the auditory nerve neurophonic to low frequencies and the CAP to high frequencies. Cases with larger CAPs had smaller SPs. The correlation of ECochG-TR, with word recognition score (WRS), was moderate (r = 0.67), as well as the correlation between pure-tone averages and ECochG (r = 0.63). The cochlea remained functional in two cases of sudden sensorineural hearing loss with 0% WRS. Conclusion: Reduced ECochG-TR and neural activity in many cases indicates both sensory and neural deficits. Smaller SPs when CAPs are present indicate a neural contribution to the SP. Good cochlear function with 0% WRS, and cases of sudden sensorineural hearing loss with retained cochlear function, indicate retrocochlear effects, typically proximal to the spiral ganglion cells.